DAMPAK VIDEO PEMBELAJARAN BILINGUAL BERBASIS INSHOT TERHADAP HIGH ORDER THINKING SKILL DAN PENGAMBILAN KEPUTUSAN - Nendra, Fadly; Imelia Ardani, Tusti; Nadira; Anggelia Putri, Dinka; Netriwati; Rosidah, Mar'ati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the impact of using bilingual learning videos based on the Inshot application on students' High Order Thinking Skills (HOTS) and decision-making abilities. The background of this study is based on the low level of higher-order thinking and decision-making skills among students, as well as the need for innovative learning media that are appropriate to the context of Islamic institutions. The study used a quantitative method with a quasi-experimental design, involving two classes (control and experimental) with a total of 44 students. The research instrument was a validated and reliable essay test (Cronbach's Alpha = 0.970). Data analysis was conducted using MANOVA to test two dependent variables simultaneously. The results showed that bilingual learning videos based on Inshot had a significant effect on improving students' HOTS and decision-making abilities. These findings support the use of simple technology designed contextually as an alternative learning media that is effective and relevant to the characteristics of institutions.